The green price and its effect on the purchasing decision of the final consumer - Chahid, Iliass; Abdlaoui, Okba; Dafrour, Abdnaim (Milev Journal of Research and Studies, 2017)
With the increasing environmental awareness of many consumers and increasing the activity of consumer movements and the emergence of green consumers, consumers become the focus of the development of green products, as the marketer begins to identify the needs and desires of consumers, and then devises strategies to meet these needs best to achieve the objectives of the institution, It is necessary to study the behavior of consumers towards green products, The price and decisions related to determining the role of pricing and its objectives, and determining the appropriate price policy of the most difficult decisions facing marketing men, because it must take into account the consumer on the one hand, and on the other achieve the objectives of the institution in integration with the rest of the elements of the marketing mix, This study analyzes green consumer behavior and its impact on green prices, and concludes that the green consumer is an environmentally friendly consumer and is willing to pay extra value for green products.